(untitled) (Bangladesh Journal of Medicine, 2015)
Background and Aims: A number of patients presenting with anaemia are referred to gastroenterologist for evaluation. Literal sense of unexplained anaemia is anemia of unknown origin, which is widely used by the clinicians. Aims of this study were to determine the underlying cause of unexplained anemia and to identify clinical features that may point to primary gastrointestinal diseases. Methods: All the patients presenting with anaemia admitted in the department of Gastroenterology from January 1990 to July 2001 were enrolled for this study. Results: Sixty two patients were included in this study, twenty two were Collected retrospectively and forty were collected prospectively. The mean Age was 43 years (SD ± 14.8, range 1572 years). Twenty eight of the Patients were male, remaining thirty four were female. The mean duration of the illness was 26.3 months (SD ± 41.8, range 1240 months) and the Mean haemoglobin was 6.4 gm/ dl (SD ± 1.2, range 3.59 gm/dl). Among 62 patients, gastrointestinal causes for anaemia were found in 32 (51.62%) patients. Seventeen (27.41%) patients had a disease outside gastrointestinal tract; in thirteen (20.96%) patients no cause for anaemia could be established. Gastrointestinal malignancy was the most common finding, Gastrointestinal tuberculosis was the next. Symptoms had a sensitivity and Specificity of upper gastrointestinal disease of 64% and 36% respectively, and 30% and 82% for colonic disease. Conclusions: Gastrointestinal malignancy frequently presents with unexplained anaemia. Symptoms are poor predictors for site specific lesion. The standard evaluation of a patient with unexplained anaemia includes a complete evaluation of the gastrointestinal tract. However, even after extensive investigations many patients may remain without a diagnosis. Bangladesh J Medicine Jan 2014; 25 (1) : 3-7